Where Things Come Back A Novel - Whaley, John Corey (New York Atheneum Books for Young Readers, 2011)
Seventeen-year-old Cullen's summer in Lily, Arkansas, is marked by his cousin's death by overdose, an alleged spotting of a woodpecker thought to be extinct, failed romances, and his younger brother's sudden disappearance.
Keywords: Missing persons; Interpersonal relations; Best friends; Friendship; Extinct birds; Family life -- Arkansas; Arkansas